2009
DOI: 10.4314/tjpr.v8i5.48090
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Pharmacological Activities of Calendula officinalis Linn (Asteraceae): A Review

Abstract: Calendula officinalis Linn. (Asteraceae) is used medicinally in Europe, China and India amongst several places in the world. It is also known as "African marigold" and has been a subject of several chemical and pharmacological studies. It is used in traditional medicine, especially for wound healing, jaundice, blood purification, and as an antispasmodic. Chemical studies have underlined the presence of various classes of compounds, the main being triterpenoids, flavonoids, coumarines, quinones, volatile oil, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
179
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(200 citation statements)
references
References 50 publications
7
179
0
14
Order By: Relevance
“…The production of the phytohormone (IAA) and siderophores by Bacillus species has been investigated in many studies. The IAA stimulates the plant growth and siderophores chelate iron (Fe) and deprive the phytopathogenic fungi of it [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Here, the Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of the phytohormone (IAA) and siderophores by Bacillus species has been investigated in many studies. The IAA stimulates the plant growth and siderophores chelate iron (Fe) and deprive the phytopathogenic fungi of it [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Here, the Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Calendula officinalis is an important medicinal herb used in Europe, China, US and India. C. officinalis has numerous medicinal properties among which it is worth mentioning the anti-inflammatory and antioedematous activities, the antibacterial and antifungal activities, the anticancer and lymphocyte activation dual activities, the anti-HIV activity, the immunostimulant activity, the antioxidant activity, the hepatoprotective activity, the wound healing activity and the antiviral activity [17]. Several phytopathogenic fungi were detected on C. officinalis seeds such Alternaria alternata, Alternaria porri, Botrytis cinerea, Drechslera (Cochliobolus) hawaiiensis, Fusarium avenaceum, Fusarium culmorum and Sclerotonia sclerotiorum.…”
Section: Introductionmentioning
confidence: 99%
“…As inflorescências são maceradas e aplicadas no local do ferimento na forma de emplasto. A utilização popular da calêndula se deve pelas suas propriedades colerética, anti-inflamatória, analgésica, antitumoral, bactericida, diurética, cicatrizante, sedativa e imunomoduladora (FRANCO, 1996), sendo que estudos científicos comprovam a propriedade antiinflamatória dessa espécie, corroborando a indicação popular (HEROLD et al, 2003;UKIYA et al, 2006;MULEY et al, 2009).…”
Section: Resultsunclassified
“…Suas flores são utilizadas em forma de chá, compressas ou extratos contra afecções dermatológicas, com ação antipruriginosa, antiinflamatória e cicatrizante, fazendo parte da composição de preparações de medicamentos para tratamento de eritemas solares, queimaduras e dermatoses secas (SIMÕES, 2003;PAGNANO et al, 2008). Outros usos estão relacionados à ação anti-inflamatória e antiulcerogênica no tratamento de inflamações do trato digestivo superior (KÖRBES, 1995;MULEY et al, 2009). …”
Section: Introductionunclassified
“…According to the obtained results, CO could not stop or reduce tissue complications and damages resulting from STZ in the kidney. Studies showed that the CO plant contains different components such as triterpenoids (saponins), flavonoids, coumarins, quinones, volatile oil, carotenoids and amino acids (38). The adverse effect of this extract on undesirable increase of blood BUN as well as on the kidney tissue in the normal rats receiving this extract could imply the toxicity of this plant.…”
Section: Discussionmentioning
confidence: 99%